Characterization of Poplar Overexpressing Xylanase - Yong Woo Park; Kei’ichi Baba; Yuzo Furuta; Keisuke Kojiro; Masato Yoshida; Takahisa Hayashi (Masyarakat Peneliti Kayu Indonesia, 2010)
We expressed Hordeum vulgare (barley) xylanase constitutively in Populus tremula x alba (poplar). The expression of xylanase reduced not only the amount of hemicellulose but also the amount of lignin in the secondary xylem. Stem and leaf growth rates were accelerated in transgenic plants. The stems also developed increased flexibility, especially in their younger parts, specifically, the regions above the 10th internode from the top. The secondary walls in the xylem would be slower to mature in xylanase-expressing poplar than in the wild type.